THE DEVELOPMENT OF EDUCATIONAL TOURISM IN THE WORLD - Otaboyeva Guzal Beymamat kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Educational tourism, a niche within the broader tourism industry, has seen significant growth in recent decades, driven by globalization, increasing demand for cross-cultural experiences, and the rise of international education opportunities. This article explores the development of educational tourism globally, highlighting key trends, the economic impact of this sector, and the challenges and opportunities for future growth.